2010
DOI: 10.1002/adfm.201001080
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Containing γ‐MnO2 (TM) Hollow Spheres: One‐Step Synthesis and Catalytic Activities in Li/Air Batteries and Oxidative Chemical Reactions

Abstract: Titanium containing γ -MnO 2 octahedral molecular sieves having hollow sphere structures are successfully prepared for the fi rst time using a one-step synthesis method. Titanium cations are used as structure-directing agents in the synthesis process. The assembly of the hollow spheres is carried out at the beginning of the process. Various techniques including XRD, N 2 adsorption, SEM, EDX, RAMAN, TEM, XPS, and TGA are employed for the materials characterization. Ti is incorporated into the MnO 2 framework in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(95 citation statements)
references
References 59 publications
2
93
0
Order By: Relevance
“…Manganese oxide, in particular, has attracted great interest because of its good ORR activity based on its high specifi c capacity and low cost. [ 8,13,23,25,27,[162][163][164] Bruce and co-workers compared the effectiveness of various crystal structures of manganese oxide and reported α-MnO 2 to have the best catalytic effect for oxygen decomposition and lithium ion coordination. [ 23 ] Moreover, they found the catalytic properties of α-MnO 2 nanowires to be superior to those of spherical MnO 2 , the latter being comparable to that of the porous carbon substrate.…”
Section: Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese oxide, in particular, has attracted great interest because of its good ORR activity based on its high specifi c capacity and low cost. [ 8,13,23,25,27,[162][163][164] Bruce and co-workers compared the effectiveness of various crystal structures of manganese oxide and reported α-MnO 2 to have the best catalytic effect for oxygen decomposition and lithium ion coordination. [ 23 ] Moreover, they found the catalytic properties of α-MnO 2 nanowires to be superior to those of spherical MnO 2 , the latter being comparable to that of the porous carbon substrate.…”
Section: Metal Oxidesmentioning
confidence: 99%
“…[ 14,15 ] Many researchers are now focusing on the development of advanced catalysts and cathode substrates to improve effi ciency and cycle life using mostly organic electrolytes. Materials used as cathode supports comprise porous carbon, [16][17][18][19] graphene, [ 20 ] carbon nanotubes (CNT) or carbon nanofi bers (CNF) [ 21,22 ] with catalysts such as metal oxides (MnO 2 , [23][24][25][26] Co 3 O 4 , [ 27,28 ] noble metals, [ 7,[29][30][31] and others. [ 32,33 ] At an industrial level, in 2009 IBM launched the "Battery 500" project, which had the ambitious aim of developing a Li/air battery that could ensure a 500 mile driving range, [ 34 ] and it was thought that soon enough this technology would make it to practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Recently, hollow particles with nanoporous shells have attracted great interest because the large pore volumes and high surface areas provided by the nanoporous shells show large storage capacity and allow guest species to pass easily into the internal cavity. [8][9][10][11] For instance, metal oxide hollow particles present a superior lithium storage capacity and good cycle performance, [2a, 8] which could improve gas sensitivity [9] and catalytic performance [3a, 10] in other applications. Inspired by the superiority of nanoporous shells, the creation of microporous crystal shells with outstanding properties is also expected.…”
mentioning
confidence: 99%
“…120) Therefore, there are good grounds for the implementation of carbon-based nanomaterials; e.g., carbon nanotubes and graphene as support materials [114][115][116] to accommodate a larger amount of Li oxide. 117,118) Regarding metal nanoparticles they are good candidates as well because their catalytic properties can be considerably higher than that of bulk metals. However, it has been suggested that when the sizes of catalyst particles are within the nanometer range, specific catalyst activity does not always follow the above rationale.…”
Section: Survey Of Catalyst Research In Li-air Cellsmentioning
confidence: 99%